The zero-divisor graph with respect to ideals of a commutative semiring - Ebrahimi Atani, Shahabaddin (Array, 2008)
Abstract: In a manner analogous to a commutative ring, the ideal-based zero-divisor graph of a commutative semiring R can be defined as the undirected graph ΓI(R) for some ideal I of R. The properties and possible structures of the graph ΓI(R) are studied